2017
DOI: 10.1259/dmfr.20170037
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of alveolar and root fractures in macerated canine maxillae: a comparison between two different CBCT protocols

Abstract: Our findings demonstrated that the elected protocol for the diagnosis of root and alveolar fractures was N. This protocol allowed similar diagnosis results than HD protocol; however, with a lower amount of radiation exposure for the patient (5.6 mGy for N vs 7.0 mGy for HD).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 49 publications
0
4
0
2
Order By: Relevance
“…In general, the authors report that images obtained with smaller voxel sizes are more accurate for the diagnosis of these conditions. In contrast, Kobayashi-Velasco et al 17 and Sönmez et al 18 who evaluated the influence of the voxel size on the diagnosis of root and alveolar fracture and diagnosis of external root resorption, respectively, did not observe the influence of voxel size in their studies. Considering the possible presence or absence of voxel size influence on diagnostic tasks, the present study was developed to evaluate whether voxel size interferes with the accuracy of linear measurements on CBCT images.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In general, the authors report that images obtained with smaller voxel sizes are more accurate for the diagnosis of these conditions. In contrast, Kobayashi-Velasco et al 17 and Sönmez et al 18 who evaluated the influence of the voxel size on the diagnosis of root and alveolar fracture and diagnosis of external root resorption, respectively, did not observe the influence of voxel size in their studies. Considering the possible presence or absence of voxel size influence on diagnostic tasks, the present study was developed to evaluate whether voxel size interferes with the accuracy of linear measurements on CBCT images.…”
Section: Discussionmentioning
confidence: 90%
“…The lack of influence on the diagnosis may be associated with the acquisition of images that present enough high spatial resolution, as it happened in the studies by Kobayashi-Velasco et al 17 and Sönmez et al, 18 in which the authors did not observe the influence of voxel size in the detection of conditions. However, the largest voxel used in these studies was 0.20 mm.…”
Section: Discussionmentioning
confidence: 98%
“…Although systematic reviews have reported that the sensitivity and specificity of CBCT are about 75% to 84% and 64% to 65%, respectively (Chang et al, 2016;Talwar et al, 2016), a more recent study detected 24% sensitivity when analysing unmanipulated radiographic images and 80% sensitivity for volumetric analysis, demonstrating a good ability to identify VRF (Aristizabal-Elejalde et al, 2020). Of note, we used a voxel of 0.2 mm, as recommended by other studies (Hassan et al, 2009;Kobayashi-Velasco et al, 2017;Wenzel et al, 2009). Wenzel et al (2009) and Özer (2011), when comparing voxel tomographs with 0.12 and 0.25 mm and 0.1 and 0.19 mm, respectively, did not detect statistical differences.…”
Section: Discussionmentioning
confidence: 99%
“…FOV büyüdükçe, sabit olan matriks içindeki piksellerin boyutları geniĢler ve görüntünün geometrik çözünürlüğü azalır. 5,11 Matriks sayısını değiĢtirmeden geometrik çözünürlüğün azalması önlenmek istenildiğinde, odaklama (zooming) adı verilen ve incelenecek objenin bir bölümüne yönelik netleĢtirme (fokuslama) uygulaması yapılabilir. 12 DĠġ HEKĠMLĠĞĠNDE DĠJĠAL GÖRÜNTÜLEME SĠSTEMLERĠ DiĢ hekimliğinde geleneksel radyografi uygulamaları önemini korumakla birlikte, dijital radyografinin sağladığı avantajlar diĢ hekimlerinin dijital radyografiye olan ilgisini artırmakta ve günümüzde dijital sistemler konvansiyonel sistemlerin yerini almaktadır.…”
unclassified